Sudden Stops and Collateral Constraints: Searching for "Wally" - Pierri, Damián (2018)
Is there a connection between a sudden stop and debt issuance per year? We provide a positive answer to this question using a novel database. We find that countries that experienced a current account deficit of 7% or more during 2 to 3 year will suffer a sudden stop measured by a 4.7% to 5.0% consumption drop and a 4.0% current account reversal. Similarly, countries that experienced a current account deficit of 6% of the GDP or more during 4 to 5 years will suffer a sudden consumption drop ranging between 4.4% and 4.9% and a current account reversal between 3.2 and 3.8%. These findings serve can be used as a leading indicator for this type of events. Moreover, using a novel recursive equilibrium notion due to Pierri and Reffet (2018) we are able to match the event using a simple model without imposing shocks to deep parameters or an additional structure to exogenous variables, as it is sometimes done in the literature. The method captures completely the multiplicity of equilibria latent in the sequential equilibrium and provides evidence in favor of interpreting a sudden stop as a coordination event, similar to a bank run.